Evaluation of the Efficacy and Tolerability of a Fixed Dose Combination of Amlodipine And Indapamide in Patients Older Than 55 Years - Islam, Quazi Tarikul; Haque, KMHS Sirajuul; Moula, Kaniz; Ahasan, Ham Nazmul; Patwary, Md Ismail; Azad, Khan Abul Kalam; Rahman, Mujibur; Hossain, Md Zakir; Miah, M Titu; Azad, Abul Kalam (Bangladesh Journal of Medicine, 2023)
Background: There is very limited real-life data on hypertension management in Bangladeshi population. Considering this fact, this study evaluated the effectiveness of treatment with an indapamide/amlodipine single-pill combination (SPC) in Bangladeshi patients over the age of 55 years, in an OPD setting with uncontrolledsystolic hypertension in real-life clinical practice. Methods: This was a 3-month, multicenter, observational, open-label study conducted in 3 divisional cities of Bangladesh among patients with grade I or II hypertensions who were either uncontrolled on previous antihypertensive treatment or treatment-naïve. The effectiveness of indapamide/amlodipine SPC was assessed by the change in office systolic blood pressure (SBP) and the rate of target SBP (< 140 mmHg)achievement at 2 weeks, 1 month and 3 months, in four age groups: 55–59 years, 60–69 years, 70–79 years, and80 years or older. Results: The COMBINE study recruited 213 patients, of whom 185 took indapamide/amlodipine 1.5/5 mg SPC forafull three-month course of therapy.Mean age was 62.4±7.4 years, 76 men [41.1%] and 109 women [58.9%]. The absolute decrease of SBP during 3 months of taking indapamide/amlodipine single-pill combination (SPC) was 27.7 mm Hg, DBP - 10.2 mm Hg.After 3 months of treatment significant SBPdecreases from baseline were observed in each age group:”29.9 mmHg (from 156.7 to 126.8),”25.1 mmHg (from 152.7 to 127.6),”26.1 mmHg (from 152.8 to 126.7),and “ 24.5 mmHg (from 151.8 to 127.3)in the 55–59, 60–69, 70–79, and 80 years and older age groups, respectively. Conclusion: This COMBINE study results showed that indapamide/amlodipine SPC was associated with significant and rapid reductions in BP even in a different age range of Bangladeshi patients in routine clinical practice. This study result is consistent with already achieved data of this SPC globally. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 200